PELAKSANAAN PENCORETAN HAK TANGGUNGAN (ROYA) PADA SERTIPIKAT DI KANTOR PERTANAHAN KOTA PEKANBARU DALAM MEMBERIKAN KEPASTIAN HUKUM - Yuslim Yuslim; Iswandi Iswandi; Azmi Fendi (LPPM Universitas Ekasakti Padang, 2023)
A mortgage is a guarantee of debt repayment. The write-off of the Mortgage Right (Roya) on the land certificate is the most important stage. It releases the Mortgage right on the certificate and land book (archive) located at the Office of the National Land Agency (BPN) because the debt has been paid off. This legal research uses an empirical juridical approach. While this type of research is descriptive and analytical. Data collection techniques were carried out through structured interviews and document studies. The results of the study of the implementation of the deletion of mortgage rights (roya) on certificates at the Pekanbaru City Land Office in providing legal certainty, namely that there is disharmony in each of the regulations governing the timeframe for arranging mortgage rights, there are differences in working days. In the latest provisions, the type of royal management service is 3 working days for manual and 1 working day for electronic, this is by the Decree of the Minister of ATR/BPN Number 440/SK-HR.02/III/2023. The abolition of the Mortgage must be followed by the erasing of the Mortgage Right from the Land Book of land rights burdened with the Mortgage Right, it is necessary to have evidence in the form of a written statement issued by the Creditor holding the Mortgage Right, that the debt guaranteed by the Mortgage has been repaid by the Debtor or has been deleted by law, thus the Mortgage can be crossed out for registration of deletion at the Land Office.